The Difference of Nosocomial Urinary Tract Infection Risk Based on Chateterization Urine, Age, and Diabetes Mellitus - Edel Weisela Permata Sari; Prijono Satyabakti (Universitas Airlangga, 2015)
Urinary nosocomial infection is a type of nosocomial infection that often occurs in patients with fixed catheters. Factors causing nosocomial urinary tract infections include host, agent, and urinary catheterization factors. This study aims to analyze the differences in the risk of urinary nosocomial infections based on urinary catheterization, age, and diabetes mellitus (DM). This study uses a case-control design with a sample size of 20 in each case and control group. Case samples were patients diagnosed with urinary tract infections while control samples were patients who were not diagnosed with urinary tract infections at the Haji Public Hospital (RSU Haji), Surabaya from 2013 to 2014. Independent variables were a timeline of catheter placement, urinary catheterization frequency, age, and DM, while the dependent variable is nosocomial urinary tract infection. Data processing uses risk difference (RD) analysis in Epi-info. The results showed that the difference in the risk of urinary nosocomial infection based on the duration of urinary catheter installation was RD = 0.52, meaning that if a catheter replacement effort was made every 7 days, it could prevent 0.52 of 0.71 or 73.53% of urinary tract infections, the frequency of urinary catheterization of RD = 0.44 means that if efforts are made to reduce urine catheterization up to 1 time, it can prevent 0.44 of 0.79 or 55.94% of urinary tract infections, age of 0.40 means that if indicated proper installation and installation procedures in patients> 55 years old, can prevent 0.40 of 0.68 or 59.26% incidence of urinary tract infections and DM of RD = 0.42 means that if prevention efforts are made against DM, it can prevent 0.42 of 0.75 or 55.56% incidence of urinary tract infections.